Pathological and Biochemical Alteration in COVID-19 - Noni Gopal Singha (Assam Journal of Internal Medicine)
Corona virus disease 2019 (COVID-19) caused by severe acute respiratory corona virus 2 (SARS-COV-2) is mainly respiratory disease occurring since December 2019 and first detected in Wuhan province of China. The complexity of SARSCOV-2 is centered on the unpredictable clinical course of the disease that can rapidly develop causing severe and deadly outcomes. The pandemic COVID-19 is a scientific, medical, and social challenge. In this review, the basic pathological and biochemical changes in COVID-19 are described, also how it influences in predicting the disease progression thereby helping in early interventions to prevent complications.